What the signboard hides: food, caste and employability in small South-Indian eating places - Iversen, Vegard; Raghavendra, P. S. (SAGE Publications, 2006)
In India, there are strong and intimate links between traditional notions of caste, purity and pollution and the preparation and consumption of food. This article studies trajectories of social change within small South Indian eating places, popularly known as Udupi hotels. During the second half of the 20th century such enterprises absorbed a large number of unskilled migrants, mainly from Karnataka's coastal belt. We explore the relationship between caste and employability within the industry and the impact of caste on individual career progress. Combining case studies of enterprises from villages, small towns and cities with data from in-depth interviews with a sample of hotel workers, we argue that small South Indian eating places are elusive social arenas that can shed new light on the nature, persistence and change in caste-based exclusion in important markets for unskilled labour in modern India.